Unravelling Digital Crime Scenes: Pedagogical Strategies in Digital Forensics PBL - Venkatesh, K.; Rajasubramanian, R.; Manikumar, T.; Mohideen, Akbar Badhusha (Journal of Engineering Education Transformations, 2025)
The DIGIT framework emphasizes spanning the gap between digital forensics theory and real-world challenges through PBL assessment and teaching methods. To develop the practical skills, this method uses interactive exercises like simulated cybercrime investigations and data recovery assignments. Summative evaluations, such as investigative reports and practical tests, guarantee thorough evaluation, while formative assessments, such as peer reviews and reflective journals, offer ongoing feedback. Students were organized into 18 groups, focusing on activity recognition in various domains such as data acquisition, evidence analyser, and reporting and presentation for PBL. With the help of this approach, students can confidently and competently handle challenging forensic situations. To establish a dynamic and engaging learning environment that reflects real-world problem-solving, evaluation and pedagogies are used in problem-based learning (PBL). With the goal of measuring both the process and results of student learning, assessments guarantee a thorough assessment of abilities and knowledge. In order to help students connect with the material on a deep level, pedagogies are created to encourage teamwork, creativity, and critical thinking. The course resulted in six live solutions, with two projects submitted for patents and six converted into research publications. Qualitative feedback indicated high levels of student satisfaction, with 88% reporting increased engagement and 89% feeling better prepared for real-world applications. Future research should investigate the scalability of this approach across various engineering disciplines and evaluate its long-term impact on students' career.